Presynaptic mechanisms controlling calcium-triggered transmitter release at the neuromuscular junction. Issue 4 (August 2018) - Dittrich, Markus; Homan, Anne E; Meriney, Stephen D
Highlights: The positioning of Ca 2+ channels relative to synaptic vesicles determines function. The Ca 2+ -release relationship can be explained by an excess of calcium binding sites. Action potential shape indirectly influences calcium entry at the synapse. Low probability of Ca 2+ channel opening and Ca 2+ ion-triggered fusion governs release. Active zone heterogeneity likely characterizes neuromuscular junction function. Abstract : Calcium-triggered neurotransmission underlies most communication in the nervous system. Yet, despite the conserved and essential nature of this process, the molecular underpinnings of calcium-triggered neurotransmission have been difficult to study directly and our understanding to this date remains incomplete. Here we frame more recent efforts to understand this process with a historical perspective of the study of neurotransmitter release at the neuromuscular junction. We focus on the role of calcium channel distribution and organization relative to synaptic vesicles, as well as the nature of the calcium sensors that trigger release. Importantly, we provide a framework for understanding how the function of neurotransmitter release sites, or active zones, contributes to the function of the synapse as a whole.